The XBB.1.5 mRNA booster vaccine does not significantly increase the percentage of XBB.1.5 mono-reactive T cells - Sop, Joel; Mercado, Alicia; Figueroa, Alexis; Beckey, Tyler P.; Traut, Caroline C.; Zhang, Li; Smith, Kellie N.; Blankson, Joel N. (Frontiers in Immunology, 2025)
Recent efforts in vaccine development have targeted spike proteins from evolving SARS-CoV-2 variants. In this study, we analyzed T cell responses to the XBB.1.5 and BA.2.86 subvariants in individuals who previously received bivalent vaccines containing mRNA for ancestral and BA.5 spike proteins. T cell-mediated cytokine responses to spike proteins from both variants were largely preserved. To determine the mechanism of this preserved recognition, we utilized the functional expansion of specific T cells (FEST) assay to distinguish between the presence of T cells that cross-recognized ancestral and variant epitopes versus distinct populations of T cells that were mono-reactive for ancestral or variant epitopes. We found the majority of spike-specific T cells cross-recognized the ancestral spike and the XBB.1.5 and BA.2.86 subvariants, with less than 10% of T cells being mono-reactive for either variant. Interestingly, immunization with the XBB.1.5 monovalent booster vaccine did not significantly increase the percentage of XBB.1.5 mono-reactive T cells. Our results suggest a potential limitation in the induction of mono-reactive T cell responses by variant-specific booster vaccines.